African Disability Rights Yearbook Volume 5 2017 - Charles Ngwena (Pretoria University Law Press (PULP), 2017)
The African Disability Rights Yearbook addresses disability rights within the foundational structure laid down by the inaugural issue. The structure comprises a tripartite division between: articles; country reports; and shorter commentaries on recent regional and sub-regional developments. The African Disability Rights Yearbook aims to advance disability scholarship. Coming in the wake of the United Nations Convention on the Rights of Persons with Disabilities, it is the first peer-reviewed journal to focus exclusively on disability as human rights on the African continent. It provides an annual forum for scholarly analysis on issues pertaining to the human rights of persons with disabilities. It is also a source for country-based reports as well as commentaries on recent developments in the field of disability rights in the African region. The African Disability Rights Yearbook publishes peer-reviewed contributions dealing with the rights of persons with disabilities and related topics, with specific relevance to Africa, Africans and scholars of Africa. The Yearbook appears annually under the aegis of the Centre for Human Rights, Faculty of Law, University of Pretoria. The Yearbook is an open access online publication, see www.adry.up.ac.za